Y = x

y = (x

y + 13 = (x + 4)

This is "vertex form" where the vertex is (-4, -13)

The roots are the values of x that make y=0,

(0) + 13 = (x + 4)

±√13 = x+4 (take the square root of both sides)

-4±√13 = x (subtract 4 from both sides)

The roots are -4-√13, -4+√13

^{2}+ 8x + 3y = (x

^{2}+ 8x + 16) + (3 - 16) (complete the square)y + 13 = (x + 4)

^{2}(add 13 to both sides, show the square we completed)This is "vertex form" where the vertex is (-4, -13)

The roots are the values of x that make y=0,

(0) + 13 = (x + 4)

^{2}(substitute y=0, so we can solve for x)±√13 = x+4 (take the square root of both sides)

-4±√13 = x (subtract 4 from both sides)

The roots are -4-√13, -4+√13